Envisioning Future Elementary School Teachers’ Practices in The Post-Pandemic Era: A Visual Narrative Inquiry - Mahmud, Yogi Saputra (Universitas Pendidikan Ganesha, 2023)
The COVID-19 pandemic has revolutionised the educational landscape massively, including the way teachers enact their roles both inside and outside the classroom context. The abrupt changes also influence pre-service teachers’ way of envisioning themselves as future teachers in the post-pandemic era. The aims of this study is to analyze the underlying influences and concerns for their choice of future projection as post-pandemic elementary school teachers. This study using the photo-narrative frame construct of visual narrative inquiry, this study explored the way three first-year pre-service elementary school teachers imagined their. The data were collected from students’ self-portraits and written narratives narrating their past, current, and future projection as post-pandemic teachers. The multimodal narrative analysis was applied to analyse both the visual and written narratives. The findings suggest that technology integration and student-centred pedagogy became the most common themes when the pre-service teachers projected their future selves. At the same time, their previous schooling experiences and future concerns about becoming a teacher had certain impacts on the way they projected themselves as future teachers. Therefore, it is recommended that future pre-service teachers should be given opportunities to reflect on their previous teaching and learning experiences and project what they wish to emulate and enhance for their future teaching practices.